2005
DOI: 10.1111/j.1365-2141.2005.05512.x
|View full text |Cite
|
Sign up to set email alerts
|

The course of ADAMTS‐13 activity and inhibitor titre in the treatment of thrombotic thrombocytopenic purpura with plasma exchange and vincristine

Abstract: Summary The therapeutic efficacy of plasma exchange (PE) in thrombotic thrombocytopenic purpura (TTP) is attributed to the restoration in ADAMTS‐13 (a disintegrin and metalloproteinase with thrombospondin motif‐13) activity by substitution of the enzyme and removal of ADAMTS‐13‐neutralizing autoantibodies. We explored this rationale by analysing ADAMTS‐13 activity and corresponding inhibitor levels during PE‐treatment in 27 episodes from 23 adults with TTP. All patients with an initial episode of TTP (n = 14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 35 publications
3
65
0
7
Order By: Relevance
“…By comparison, the fraction of autoimmune TTP with ADAMTS13 activity levels <5% that is reported in the literature varies from 33% to 100% (Furlan et al, 1998;Tsai & Lian, 1998;Veyradier et al, 2001;Vesely et al, 2003;Kremer Hovinga et al, 2004;Matsumoto et al, 2004;Zheng et al, 2004;Bohm et al, 2005;Sadler, 2008). The high sensitivity reported in this study probably reflects the stringency of our clinical definitions and our careful attention to secondary causes of TMA.…”
Section: <0á0001mentioning
confidence: 69%
“…By comparison, the fraction of autoimmune TTP with ADAMTS13 activity levels <5% that is reported in the literature varies from 33% to 100% (Furlan et al, 1998;Tsai & Lian, 1998;Veyradier et al, 2001;Vesely et al, 2003;Kremer Hovinga et al, 2004;Matsumoto et al, 2004;Zheng et al, 2004;Bohm et al, 2005;Sadler, 2008). The high sensitivity reported in this study probably reflects the stringency of our clinical definitions and our careful attention to secondary causes of TMA.…”
Section: <0á0001mentioning
confidence: 69%
“…However, contrasting results have been obtained by the few studies aimed at establishing whether ADAMTS13 testing during the acute episode helps to identify patients' prognosis and can be used to guide their management [17][18][19][20]. On this basis, there is general agreement that all patients in the acute phase have to receive the most effective treatment [21], and we suggest that, at least presently, the best option is represented by concomitant PE and high dose corticosteroids.…”
Section: Discussionmentioning
confidence: 90%
“…According to severe recent studies those kind of TTP associated with severe deficiency of ADAMTS 13 activity less mortality rate than those with detectable ADAMTS 13 [46][47][48][49]. By contrast, Coppo et al [51] reported much high mortality rate in patients with severe ADAMTS 13 deficiency in comparison to those with non-severe deficiency. Higher mortality rate of patients with detectable ADAMTS 13 activity could be related to the lethal fault of their underlying diseases.…”
Section: Classification Of Ttpmentioning
confidence: 90%
“…Define the strong relation between inhibitory anti ADAMTS 13 testing and mortality rate. Overall, we come to the conclusion that existence of anti ADAMTS 13 is associated with a worse prognosis [47][48][49][50][51]. Moreover there are some reports of a positive correlation between high inhibitor titers and severity of clinical manifestations, treatment refractoriness and the rate of deaths [48,52,53].…”
Section: Classification Of Ttpmentioning
confidence: 97%